Influence of Processing Oil Content on Rubber-Filler Interactions in Silica/Carbon Black-Filled Natural Rubber Compounding - Kusuma Arti Dewi; Donwang Wanita (E3S Web of Conferences, 2024)
To ensure the production of high-quality rubber products, establishing effective compatibility and robusting interactions between rubber and fillers is crucial. Since the rubber production industry faces significant environmental challenges, sustainability is becoming a necessity in the rubber business. Various materials, such as the presence of processing aids, might influence rubber-filler and filler-filler interactions. Petroleum oil as general processing oil has environmental issues, thus it is urgent to replace it with bio-based oil. This study addresses these concerns by investigating the impact of paraffinic oil and bio-based oil content on the interactions between silica/carbon black and natural rubber chains. Ranging from 0 to 10 phr, different dosages of these oils were employed. The rubber compound underwent milling using two rolled laboratory open mills post-blending with a laboratory internal mixer. Subsequently, mechanical properties were assessed. A Rubber Processing Analyzer was utilized to characterize interactions between uncured and cured silica/carbon black-filled natural rubber blends. The results revealed that all variations were distributed uniformly. Tan Delta results confirm that a chemical with a high bio-based oil concentration is easier to process. The carbon black with the largest peak of modulus values at low strain has the highest reinforcing or the poorest dispersion. Compounding with paraffinic oil has a high peak modulus value, resulting in poor dispersion when compared to bio-based oil. This research sheds light on the potential of bio-based oils as an eco-friendly alternative in rubber processing, contributing to sustainability efforts in the industry.